Chemotaxis‐Guided Hybrid Neutrophil Micromotors for Targeted Drug Transport. Issue 42 (7th September 2017) - Shao, Jingxin; Xuan, Mingjun; Zhang, Hongyue; Lin, Xiankun; Wu, Zhiguang; He, Qiang
Abstract: Engineering self‐propelled micromotors with good biocompatibility and biodegradability for actively seeking disease sites and targeted drug transport remains a huge challenge. In this study, neutrophils with intrinsic chemotaxis capability were transformed into self‐guided hybrid micromotors by integrating mesoporous silica nanoparticles (MSNs) with high loading capability. To ensure the compatibility of neutrophil cells with drug‐loaded MSNs, bacteria membranes derived from E. coli were coated on MSNs in advance by a camouflaging strategy. The resulting biohybrid micromotors inherited the characteristic chemotaxis capability of native neutrophils and could effectively move along the chemoattractant gradients produced by E. coli . Our studies suggest that this camouflaging approach, which favors the uptake of MSNs into neutrophils without loss of cellular activity and motility, could be used to construct synthetic nanoparticle‐loaded biohybrid micromotors for advanced biomedical applications. Abstract : Motoring in the right direction : Self‐guided biohybrid micromotors were developed by integrating natural neutrophils with mesoporous silica nanoparticles camouflaged with bacterial membranes. The hybrid species inherited the intrinsic chemotaxis capability of the neutrophils and moved autonomously along chemoattractant gradients without external energy input to transport a cargo to the targeted site.